Impact of talk shows and variety show television programs viewership on political interest among Indonesian college students - Drina Intyaswati; Fitria Ayuningtyas; Witanti Prihatiningsih; Made Oktavia Vidiyanti (Universitas Trunojoyo Madura, 2022)
Television, with a larger audience than other mass media in Indonesia, can improve youth engagement in politics, or at least their curiosity about politics. Previous studies showed inconclusive results concerning the effects of television viewing and political interest. However, the current study assessed the effect of talk shows and variety show viewership on college students’ political interests. A survey was conducted of 400 college students at Universitas Pembangunan Nasional Veteran Jakarta (UPNVJ), Jakarta, Indonesia, using a stratified sampling technique and data analysis with multiple linear regression analysis. The results verified that talk shows and variety show viewership directly relate to the political interest in youth. Variety show viewership has a negative relationship, which means that political interest decreases as viewing of variety show increases. Television use, talk show viewership, and political knowledge positively correlate with political interest. The author suggests a sample from a broader geographical area in the future. Furthermore, the conceptualization of variety shows should be examined more.